LOCAL WISDOM VALUES OF MALAQBI AS THE FORMATION OF MANDAR ETHNIC CHARACTER - Nasir, Muhammad; Danial, Muhammad; Azis, Ahmad Ridhai; Adawiah, Rabiatul (Balai Penelitian dan Pengembangan Agama Makassar, 2024)
This research aims to describe the value of local wisdom